2018
DOI: 10.1038/s41467-018-06744-7
|View full text |Cite
|
Sign up to set email alerts
|

A phosphatidylinositol 4,5-bisphosphate redistribution-based sensing mechanism initiates a phagocytosis programing

Abstract: Phagocytosis is one of the earliest cellular functions, developing approximately 2 billion years ago. Although FcR-based phagocytic signaling is well-studied, how it originated from ancient phagocytosis is unknown. Lipid redistribution upregulates a phagocytic program recapitulating FcR-based phagocytosis with complete dependence on Src family kinases, Syk, and phosphoinositide 3-kinases (PI3K). Here we show that in phagocytes, an atypical ITAM sequence in the ancient membrane anchor protein Moesin transduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 68 publications
3
41
0
Order By: Relevance
“…However, considering that ERMs can also work as protein-associated modules to transmit signaling through the binding of the Src kinase Syk to the immunoreceptor tyrosine-based activation motif (ITAM) of their FERM domain [110], a provocative study has suggested that ERMs may stimulate phagocytosis through receptor-independent mechanisms. In this way, they would act as phylogenetically conserved mechanotransducers that activate PI3K in response to the deformations of the PM, which accumulate PIP 2 at the contact sites with foreign cells and particles, recruiting ERMs to the emerging phagocytic cup [111]. Nevertheless, while ERMs can regulate phagocytosis through a signaling pathway similar to that triggered by the ITAMs of FcγRs, the absence of moesin does not disturb internalization of IgG-coated particles, suggesting that ERMs are not essential for opsonization-mediated internalization.…”
Section: The Phagocytic Cup and The Phagosomementioning
confidence: 99%
See 1 more Smart Citation
“…However, considering that ERMs can also work as protein-associated modules to transmit signaling through the binding of the Src kinase Syk to the immunoreceptor tyrosine-based activation motif (ITAM) of their FERM domain [110], a provocative study has suggested that ERMs may stimulate phagocytosis through receptor-independent mechanisms. In this way, they would act as phylogenetically conserved mechanotransducers that activate PI3K in response to the deformations of the PM, which accumulate PIP 2 at the contact sites with foreign cells and particles, recruiting ERMs to the emerging phagocytic cup [111]. Nevertheless, while ERMs can regulate phagocytosis through a signaling pathway similar to that triggered by the ITAMs of FcγRs, the absence of moesin does not disturb internalization of IgG-coated particles, suggesting that ERMs are not essential for opsonization-mediated internalization.…”
Section: The Phagocytic Cup and The Phagosomementioning
confidence: 99%
“…Nevertheless, while ERMs can regulate phagocytosis through a signaling pathway similar to that triggered by the ITAMs of FcγRs, the absence of moesin does not disturb internalization of IgG-coated particles, suggesting that ERMs are not essential for opsonization-mediated internalization. On the contrary, ERMs seem to improve phagocytosis mediated by those mechanisms in which neither opsonization nor ITAM-bearing receptors are involved, such as the clearance of microorganisms and apoptotic cells by direct binding of scavenger receptors and receptors of phosphatidyl serine (PS), respectively [111]. Although attractive, the mechanotransduction model by which the PIP 2 -ERM-ITAM-Syk axis may collaborate with receptor-mediated opsonisation-independent phagocytosis leads to some unanswered questions.…”
Section: The Phagocytic Cup and The Phagosomementioning
confidence: 99%
“…However, Clec12A is an inhibitory receptor that limits inflammatory responses, while potentiating type I interferon (IFN) responses [13][14][15] . Independent of recognition by receptors, MSU crystals activate immune cells by interacting with membrane cholesterol 16 or inducing membrane deformation 17 . Under physiological conditions, opsonization of the crystals with complement or other opsonins may also eliminate the need for specific crystal receptors.…”
mentioning
confidence: 99%
“…IP3 is a key regulator of the cytoplasmic Ca 2+ concentration by controlling a Ca 2+ channel IP3 receptor on the endoplasmic reticulum (ER) . In addition to being the precursor of DAG and IP3, PI(4,5)P2 is also a key messenger that regulates the polymerization of the actin cytoskeleton, plasma membrane tension, exocytosis, membrane fusion, activity of ion channels, and cell adhesion, etc . Thus, PI(4,5)P2 is of great importance during receptor signaling and cell activation.…”
Section: Basic Roles Of Pi(45)p2 In Receptor Activationmentioning
confidence: 99%